Pengaruh Penggunaan Fungisida (Dithane M-45) Terhadap Pertumbuhan Tanaman Jagung (Zea mays L.) dan Kepadatan Spora Fungi Mikoriza Arbuskula (FMA) - Endah Mutia Sari; - Suwirmen; Zozy Aneloi Noli (Jurnal Biologi Universitas Andalas, 2014)
The research about effect of fungicide (Dithane M-45) on growth of corn (Zea mays L.) and spore density of arbuscular mycorrhizal fungi (AMF) had been done from August to November 2013 in a wire house at Laboratory of Plant Physiology, Departement of Biology, Faculty of Sciences, Andalas University. The research used Completely Randomized Design (CRD) with 7 treatmens and 4 replications. The treatments were varions doses of Dithane M-45; A (0 g/l), B (1,5 g/l), C (2,0 g/l), D (2,5 g/l), E (3,0 g/l), F (3,5 g/l), G (4,0 g/l). The results showed that Dithane M-45 decreased height and number of leaves of corn plants, leaf dry weight and spore density of AMF. The higher doses of fungicide used the fewer spores were obtained.Keywords: mycorrhizal, fungicide, Zea mays